A conifer–angiosperm divergence in the growth vs. shade tolerance trade‐off underlies the dynamics of a New Zealand warm‐temperate rain forest. (9th January 2015) - Lusk, Christopher H.; Jorgensen, Murray A.; Bellingham, Peter J.; Gilliam, Frank
Summary A central tenet of forest ecology is that succession and regeneration dynamics are driven by an interspecific trade‐off between juvenile growth rates in high light and shade tolerance. There is evidence, however, that a single trade‐off axis may fail to explain the dynamics of mixed conifer–angiosperm rain forests in the Southern Hemisphere, especially in New Zealand. We tested for growth vs. shade tolerance trade‐offs by measuring juvenile growth of five podocarps and five broadleaved canopy angiosperms across a wide range of light environments in a New Zealand warm‐temperate rain forest. The light compensation point of growth was used as a measure of species light requirements, which we then compared with height growth in 10% light, approximating the environments encountered beneath small treefall gaps. Despite considerable overlap between the ranges of both growth rates and compensation points found in the two lineages, major axis tests showed that the growth vs. shade tolerance trade‐off differed significantly between podocarp and angiosperm species. At a common compensation point, angiosperms were faster growing than podocarps in 10% light. However, juveniles of these angiosperm species were notably scarce in the more open environments associated with forest margins. Synthesis. A conifer–angiosperm divergence in the growth vs. shade tolerance trade‐off may explain long‐standing problems of the dynamics of these forests. Although juveniles of most lowland podocarps can tolerate considerable shade, the more vigorous response of broadleaved angiosperms to small canopy openings enables them to out‐compete podocarps in old‐growth stands. The greater abundance of podocarp juveniles on forest margins cannot be attributed to them out‐competing angiosperm species where light is abundant and is likely to reflect superior resistance to frost and/or drought. The drivers of the dynamics of New Zealand's podocarp–broadleaved forests therefore differ appreciably from those ascribed to tropical and north‐temperate forests.